2008
DOI: 10.1007/s11119-008-9065-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting farmer adoption of remotely sensed imagery for precision management in cotton production

Abstract: This research evaluated the factors that influenced cotton (Gossypium hirsutum L.) producers to adopt remote sensing for variable-rate application of inputs. A logit model estimated with data from a 2005 mail survey of cotton producers in 11 southern USA states was used to evaluate the adoption of remote sensing. The most frequently made management decisions using remote sensing were the application of plant growth regulators, the identification of drainage problems and the management of harvest aids. A produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 14 publications
10
49
0
7
Order By: Relevance
“…This was considered to be a consequence of older farmers having shorter planning horizons, diminished incentives to change and less exposure to PATs, mainly due to their hesitation to use the computer (Roberts et al [9]). In this context, younger farmers were postulate as having longer career horizon and being more technologically orientated (Larson et al [13]). Other studies, on the other hand found age as a positive determinant (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This was considered to be a consequence of older farmers having shorter planning horizons, diminished incentives to change and less exposure to PATs, mainly due to their hesitation to use the computer (Roberts et al [9]). In this context, younger farmers were postulate as having longer career horizon and being more technologically orientated (Larson et al [13]). Other studies, on the other hand found age as a positive determinant (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used the random utility model framework to study adoption decisions (Rahm & Huffman, 1984;Roberts et al, 2004;Larson et al, 2008;Walton et al, 2008;Jara-Rojas, Bravo-Ureta, Engler, & Diaz, 2013;Lambert et al, 2014), where a producer adopts a technology when the expected utility of profits is higher for the adoption scenario compared to the non-adoption scenario. Let E U π AG (E U π NAG ) be the expected utility of profits of adopting (non-adopting) AG systems for producer i.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Variables previously identified as factors influencing the decision to adopt PA technologies include age, education, farm size, sources used to obtain PA information, and the use of best management practices (BMPs). Banerjee et al (2008), Larson et al (2008), Walton et al (2008), and D'Antoni, Mishra, and Joo (2012) included age in the adoption equations and found that younger farmers with longer planning horizons were more likely to adopt PA technologies than older producers. Thus, farmer age (AGE) was hypothesized to have a negative effect on the adoption of ASC technologies and AG systems.…”
Section: Empirical Modelmentioning
confidence: 99%
“…As there is no clearly dominant approach in the literature, we opted to use the more traditional ordered probit procedure with thresholds not varying with respondent characteristics. 7 Readers interested in more detail about the sampling procedures, the survey methods and the rest of the survey instrument are referred toRoberts et al (2002) 8 The 2001 survey data used in this study are collected the same way as the data inLarson et al (2008), which were published in a recent issue of the Precision Agriculture Journal. Hence, the survey also asked questions about adoption of various precision technologies (i.e.…”
mentioning
confidence: 99%